Politics and trade in Africa : Does Sino-African trade and investment significantly influence Africa's United Nations General Assembly voting behaviour? - Ellis, Charlotte (School of Economics, 2016)
This paper is concerned with the political consequences of China's rapidly growing economic engagement in Africa. Whilst there has been much debate regarding the economic impact of China, few studies have been concerned with the foreign policy consequences of Sino-Africa trade relations. Using a panel of ten Sub-Saharan countries, this paper builds on the theoretical understanding of dependency theory, to explore the relationship between economic dependence and political alignment in the United Nations General Assembly (UN General Assembly). This research seeks to provide an understanding of whether states that rely heavily on China's export market are more likely to converge with China on foreign policy decisions. Acknowledging that convergence of votes with China will have implications for the United States, particularly in light of consistent foreign policy divergence between China and the US, this paper evaluates whether changes in trade relations with the US or US aid disbursements have a negative effect on voting alignment with China. The research includes two specific time periods, 1971-2011 and 2000- 2011, which isolates the effect of China's rapid emergence in the global economy and Africa in particular. Statistical analysis of the data prior to 2000 yields less convincing evidence of the relationship between export dependence and foreign policy convergence in the UN General Assembly. However, in the period thereafter, both export dependence on China and FDI from China have come to hold explanatory power in convergence of trade relations with voting convergence. Is China knowingly or unknowingly creating a level of export dependence as a way of bolstering support in the multilateral arena? Using ordinary least squares and fixed effects this paper finds evidence that greater trade in terms of exports to China promotes foreign policy convergence amongst SSA countries.